Nursing of a patient with Goodpasture’s syndrome combined with latent tuberculosis infection (1例肺出血-肾炎综合征合并结核潜伏感染患者的护理体会) - QIU Lidi (邱利娣) (中西医结合护理)
This article shared the intensive care experience of a patient with Goodpasture’s syndrome combined with latent tuberculosis infection. Key issues of nursing included monitoring of vital signs, psychological care, non-invasive ventilator use and related nursing management, plasmapheresis and related nursing, control of latent tuberculosis infection, nutrition support and prevention of pressure injuries. (本文总结1例肺出血-肾炎综合征合并结核潜伏感染的护理经验, 包括生命体征及心肝肾肺等重要脏器功能监测、重症监护室患者心理辅导、无创呼吸机使用护理、血浆置换相关护理、结核潜伏感染护理、营养支持护理、压力性损伤预防护理。)